2010
DOI: 10.1590/s1413-86702010000200007
|View full text |Cite
|
Sign up to set email alerts
|

Frequency and antimicrobial susceptibility of Shigella species isolated in Children Medical Center Hospital, Tehran, Iran, 2001-2006

Abstract: We declare no confl ict of interest. ABSTRACTAppropriate antimicrobial treatment of shigellosis depends on identifying its changing resistance pattern over time. We evaluated 15,255 stool culture submitted from July 2001 to June 2006 to the Laboratory of Children Medical Center Hospital. Specimen culture, bacterial identifi cation, and disk diffusion susceptibility testing were performed according to National Committee for Clinical Laboratory Standards guidelines. From 15,255 stool samples, 682 (4.5%) were pos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

6
8
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 26 publications
6
8
0
Order By: Relevance
“…in their study was higher than our study (5.1% vs 2.27%) that may reflect the increasing hygiene levels in our region than that reported by Jomezadeh et al Nevertheless, the frequency rate of Shigella spp. in our study was higher than those reported in other reports,19,20 but was comparable to a previous study in Iran 17…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…in their study was higher than our study (5.1% vs 2.27%) that may reflect the increasing hygiene levels in our region than that reported by Jomezadeh et al Nevertheless, the frequency rate of Shigella spp. in our study was higher than those reported in other reports,19,20 but was comparable to a previous study in Iran 17…”
Section: Discussionsupporting
confidence: 86%
“…The local epidemiology of Shigella spp. is changing over time 17. In our study, the prevalence rate of Shigella spp.…”
Section: Discussionmentioning
confidence: 60%
“…Identifying and monitoring the local resistance patterns of S. sonnei can provide effective empiric treatment regimens. The resistance rates and single-and multidrug resistance of S. sonnei isolates in Beijing were higher than those reported in other developed and developing countries (Ozmert et al, 2011;Pourakbari et al, 2010;Talukder et al, 2006;Wong et al, 2010;Wu et al, 2009). Our study results revealed that drug resistance occurred in all antibiotics tested with S. sonnei.…”
Section: Discussionmentioning
confidence: 58%
“…The results showed that the highest and lowest resistance to ampicillin and gentamicin/ciprofloxacin in S. flexneri were 85.7% (n=6/7) and 14.3% (n=1/7), respectively. Pourakbari et al reported that S. flexneri was more multiresistant than other species [ 14 ]. Results by Zhu et al [ 15 ] showed that resistance of S. sonnei to ampicillin and ciprofloxacin varied and was relatively infrequent, while antimicrobial resistance was common in S. flexneri .…”
Section: Discussionmentioning
confidence: 99%